An ideal image: effusive constrictive pericarditis - Mohd Shah, Azarisman Shah; Richardson, James D.; Chua, S. K.; Cunningham, Michael S.; Teo, Karen S.; Worthley, Stephen G. (Elsevier Inc., 2013)
Presentation